1994
DOI: 10.1046/j.1471-4159.1994.63031003.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Glutamate During Focal Cerebral Ischaemia in Rats: Time Course and Calcium Dependency

Abstract: The time course of changes in extracellular glutamic acid levels and their Ca2+ dependency were studied in the rat striatum during focal cerebral ischaemia, using microdialysis. Ischaemia‐induced changes were compared with those produced by high K+‐evoked local depolarization. To optimize time resolution, glutamate was analysed continuously as the dialysate emerged from the microdialysis probe by either enzyme fluorimetry or biosensor. The Ca2+ dependency of glutamate changes was examined by perfusing the prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(47 citation statements)
references
References 63 publications
3
44
0
Order By: Relevance
“…However, these changes are much less severe in the ischemic penumbra (Lipton, 1999). Extracellular glutamate concentrations in penumbral tissue are elevated to a lesser extent than in the core (Wang et al, 2001), estimated at 30-50 µM in different studies (Shimada et al, 1990;Wahl et al, 1994;Morimoto et al, 1996).…”
Section: Stroke: Causes Neuronal Injury and Increased Glutamate And Cmentioning
confidence: 98%
See 2 more Smart Citations
“…However, these changes are much less severe in the ischemic penumbra (Lipton, 1999). Extracellular glutamate concentrations in penumbral tissue are elevated to a lesser extent than in the core (Wang et al, 2001), estimated at 30-50 µM in different studies (Shimada et al, 1990;Wahl et al, 1994;Morimoto et al, 1996).…”
Section: Stroke: Causes Neuronal Injury and Increased Glutamate And Cmentioning
confidence: 98%
“…In the ischemic core, extracellular glutamate has been estimated to increase from a physiological level of 5 µM to values ranging from 100 µM to 10 mM (Graham et al, 1990;Wahl et al, 1994;Rusakov & Kullmann, 1998), which leads to excessive glutamate receptor activation. Excessive activation of glutamate receptors further enhances the anoxic depolarization and Ca 2+ influx.…”
Section: Stroke: Causes Neuronal Injury and Increased Glutamate And Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for both vesicular (Drejer et al 1985;Hershkowitz et al 1993) and non-vesicular (Szatkowski et al 1990;Pocock and Nicholls 1998) glutamate release during ischemia have been provided. It appears that in the early phase of ischemia, glutamate is released by a Ca 2+ -dependent vesicular mechanism (Katayama et al 1991;Wahl et al 1994;Pocock and Nicholls 1998;Asai et al 2000), which is followed by a Ca 2+ -independent non-vesicular release (Sanchez-Prieto and Gonzalez 1988; Ikeda et al 1989;Szatkowski et al 1990;Kawakami et al 2001). Real time glutamate measurement in an in vitro model of ischemia showed that glutamate uptake is inhibited within a few minutes of the onset of ischemia (Jabaudou et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in stroke and ischemia the GS activity is strongly reduced due to the drop in intracellular ATP levels but also via oxidative damage and proteolytic degradation (23,28). This may indirectly contribute to the dramatic increases in extracellular glutamate levels seen in the ischemic brain (4,13,44). At least some forms of human epilepsy and animal epilepsy models are associated with loss of the GS protein in hippocampus that may contribute to increased extracellular glutamate levels and hyperexcitability (12,15).…”
mentioning
confidence: 99%